Derecho disciplinario y seguridad jurídica - Guillamón Fernández, José Rafael; Baraja Rodríguez, Eugenio; Acale Sánchez, María (Rued@. Revista Universidad, Ética y Derechos, 2016)
Prof. Dr. José Rafael Guillamón Fernández Defensor Universitario UNED Prof. Dr. Eugenio Baraja Rodríguez Defensor Universitario UVA Profa. Dra. María Acale Sánchez Defensora Universitaria UCA